Fluid retention in the pulmonary circulation as a cause of pulmonary vein dilatation and atrial fibrillation development in chronic heart failure patients - Venera V. Kirillova (Russian Open Medical Journal)
Objective — The study objective was to perform a transthoracic echocardiographic study of the remodeling of the left atrium and the maximum and minimum diameters of pulmonary veins, as well as remodeling regression in the process of heart failure treatment, in patients with chronic heart failure (CHF) and different forms of atrial fibrillation (AF). Material and Methods — The prospective study included patients having CHF with paroxysmal AF (n=38) and permanent AF (n=36) and without arrhythmia (n=225); the patients had their maximum and minimum diameters of the pulmonary vein measured, additionally to the standard echocardiographic protocol, before and after six months of standard therapy including a loop diuretic. Results — Structural changes in the left atrium and pulmonary veins of patients with CHF having permanent atrial fibrillation were significantly more distinct than those in patients with paroxysmal AF, in patients without arrhythmia, and in the control group. A decrease in the maximum and minimum diameters of the pulmonary vein followed by termination of AF attacks within a year of observation was detected after CHF treatment with a loop diuretic in patients with paroxysmal AF and permanent AF. Conclusion — Prescribing loop diuretics to patients with pulmonary vein dilatation detected during transthoracic echocardiography in subjects with paroxysmal AF and permanent AF results in a decrease in PV diameters and termination of AF attacks in paroxysmal AF.